Pemberdayaan Nelayan Wilayah Pesisir Oleh Pemerintah Desa Banjar Kemuning Kecamatan Sedati Kabupaten Sidoarjo - Uswatun Chasanah; Ananta Prathama (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
As a maritime country, Indonesia is highly dependent on marine resources for food, livelihoods and cultural values. Most people, especially those on the coast, choose a profession as a fisherman for their livelihood. However, the welfare of fishermen has not received maximum attention from the government, one of which is the fishermen in Banjar Kemuning Village, Sedati District, Sidoarjo Regency. This study aims to determine the empowerment of fishermen in coastal areas by the Banjar Kemuning Village Government, Sedati District, Sidoarjo Regency. The research method used in this research is descriptive qualitative with data collection techniques in the form of interviews, documentation and observation. The focus of research in this study uses 4 (four) of 6 (six) concepts according to Mardikanto's theory (2014). The results showed that: 1) Institutional improvements carried out by the Banjar Kemuning Village Government were rebuilding KUB, developing business partnership networks, and being a liaison between fishermen and the agency to obtain capital assistance. 2) Improvements of business carried out by the Banjar Kemuning Village Government, namely forming a new business unit in KUB, namely Vannamei shrimp cultivation, but in this activity the participation of fishermen is still lacking. 3) The improvement in income is only limited to become a mediator for get assistance and capital loans. 4) Environmental improvement carried out is establishing a "Healthy Village House", but it has not been maximized in improving the physical environment because disposal of waste shells and shellfish stripping sites have not been properly and adequately repaired. Kata Kunci:iujhifdshjdfshh Abstract cjhshjldhjlsdfjlsdfjklnjsfdnjkdfsdjfkjkfdhjkfdkjhsfdhjhifdshifdhi